Avaliação da depressão miocárdica por meio do feature tracking bidimensional em cadelas com sepse - Figueiredo, Vânia Chaves (2015)
In order to study the function of the left ventricle (LV) by means of echocardiographic exam in animals with sepsis and diagnosis the myocardial depression, twenty-nine dogs were evaluated and divided into 3 groups: group I (control), group II (female dogs with pyometra and positive sepsis) and group III (female dogs with pyometra and negative sepsis). The animals were submitted to conventional echocardiography and feature tracking (FTI-2D). There was no statistical difference between the groups, for the conventional parameters of echocardiography and tissue Doppler. Regarding the radial Strain (St), group I showed higher ventricular function at diagnosis (22,80 ± 5,80 group I; 18,45 ± 5,96 group II; 18,71 ± 9,45 group III; p=0,032). For radial Strain rate (StR), only the III group had lower mean ventricular function at diagnosis (1,90 ± 0,57 group I; 1,91 ± 0,70 group II, 1,57 ± 0,53 group III; p=0,021). For the longitudinal St, lower ventricular function was observed in groups II and III at diagnosis (11,04 ± 3,38 group I; 8,59 ± 3,97group II; 8,21 ± 1,99; p=0,048) and after 10 days of post-surgery (11,04 ± 3,38 group I; 9,00 ± 2,16 group II; 8,12 ± 2,27 group III; p=0,048). In conclusion, the FTI-2D was able to detect early alterations of the left ventricular function, suggesting myocardial depression, even in female dogs with pyometra without the clinical course of sepsis. Further studies need to be carried out to elucidate questions about the reversal of cardiac dysfunction and its influence on mortality in patients with sepsis.